Pembangunan Berbasis Pemberdayaan Masyarakat - Siti Hajar Hajar; Kholilul Kholik (CERED Indonesia, 2020)
The development program implemented by the Indonesian state is oriented towards poverty alleviation and realizing the welfare of the community in every sphere of life. This orientation is also the reason for the shift in the regional autonomy paradigm from regional development to regional development. Optimization of development that is carried out is very much needed in the development and progress of the community, especially at the village level which aims to increase the capacity of the community in achieving independence, sustainable development and social justice. Thus, one of the programs that can support these development goals is the community empowerment program. This program is believed to be able to realize community independence by creating creativity that develops the potential of the village into excellence in development. The success of this program must also be supported by community involvement in the utilization and management of the village's potential. However, this community involvement becomes an obstacle in the success of community empowerment programs, such as what has been implemented in Paluh Manan Village. Community participation is not optimal, causing the utilization and management of village potentials to be suboptimal. So, there is a need for a method that can increase community participation in community empowerment programs